Peran Lembaga Swadaya Masyarakat Dalam Pemberdayaan Masyarakat di Desa Tubanan Kecamatan Kembang Pascapembangunan PLTU Tanjung Jati B - Lifda Khoirunnisa; Yuwanto .; Puji Astuti (Journal of Politic and Government Studies, 2014)
ABSTRACTTubanan village is a village with a large number of the population in the district Kembang subdistrict of Jepara. Tubanan village is also famous for its PLTU Tanjung Jati B located in the Tubanan village. Many pros and cons with the existence of the PLTU Tanjung Jati B in the Tubanan village. The problems that occurs is hampered by land acquisition price of the land that does not comply with requests from the public. Of the problems that often occur in Tubanan village, a group of community building Non-Government Organizations (NGO) that aim to help and assist the public role in resolving cases.The purpose of this study to determine the role of Non-Government Organizations (NGO) in community development afterbuilding PLTU Tanjung Jati B in Tubanan village, Kembang districts. The method of this study used a qualitative descriptive approach-analytic.PLTU Tanjung Jati impacts both positive and negative. The community also affected by the environmental damage resulting from the operation PLTU Tanjung Jati B. In the case of course Non-Government Organizations big role and contribute in helping resolve problems that occur. Compagnie is a Non-Government Organization that is still active in the Tubanan village. This Non-Government Organization very active role for the community in solving a case. Besides development helps the community in a new job.The role of Non-Government Organizations in the Tubanan village inactive value. However, the need for improvement in terms of supervision of theNGO. So the need for cooperation by the Non-Government Organizations,community and village government in terms of solving a case.Key words : Non-Government Organization, Community Empowerment.